Im Spannungsfeld von Empathie und Respekt - Wagner-Rau, Ulrike (Pastoraltheologie, 2017)
Pastoral counselors need the ability to empathize with the situation of another person. But they must also be aware of their own limits of that ability and the lasting strangeness of the counterpart. Both aspects of pastoral care are related to the topic of humandignity.The article presents the thesis of the sociologistHans Joas on the emergence of human rights and links them with developmental lines in the understanding of Christian pastoral care. Secondly it illuminates human rights as a moment of critical inquiry to pastoral practice. Finally it reflects on the possibilities of pastoral care for the protection and respect of human dignity and human rights